Hubungan antara Karakteristik Kepribadian dan Gangguan Perilaku pada Remaja - Siti Khusnul Faizah (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2022)
A balanced adolescent chooses activities that contribute to character development, increasing self-confidence, developing socializing skills, identifying passions and making decisions. The main purpose of the paper was to identify some dimensions in the personality structure of adolescents that correlate with other aspects of behavior. The evaluation and treatment of internalizing disorders in children and adolescents has a long and rich tradition in the psychology and clinical psychiatry of the child. However, the use of longitudinal data to elucidate the evolution and outcome of these conditions, as well as their assessment and treatment, is less developed in the embryonic development stage. However, there have been interesting developments and significant progress has been made. Outsourcing behaviors and disorders, due to their excessive or obvious nature, attract the attention of parents, teachers or others in the adolescent environment. However, there are situations where a subclinical, but significant, level of such a disorder goes unnoticed or is listed as a manifestation of the adolescent's level of adaptation. In this way, certain antisocial behaviors, such as theft, lying, destruction, violent tendencies, may remain unknown to parents or other adults. In some unfortunate cases, these outsourcing behaviors are recognized only after their occurrence, as elements of a pathology that culminated in tragic results. Similarly, certain behaviors of minor importance, but persistent, may foresee the subsequent occurrence of more serious or frequent violations of social rules and norms. Therefore, early identification of externalizing disorders at school, in the community, or in clinical institutions is extremely important for intervention and prevention efforts. Keywords. adolescent, personality, disorder, behavior.